Genome-wide associations for benign prostatic hyperplasia reveal a genetic correlation with serum levels of PSA. Issue 1 (December 2018) - Gudmundsson, Julius; Sigurdsson, Jon; Stefansdottir, Lilja; Agnarsson, Bjarni; Isaksson, Helgi; Stefansson, Olafur; Gudjonsson, Sigurjon; Gudbjartsson, Daniel; Masson, Gisli; Frigge, Michael; Stacey, Simon; Sulem, Patrick; et al.
Abstract Benign prostatic hyperplasia and associated lower urinary tract symptoms (BPH/LUTS) are common conditions affecting the majority of elderly males. Here we report the results of a genome-wide association study of symptomatic BPH/LUTS in 20, 621 patients and 280, 541 controls of European ancestry, from Iceland and the UK. We discovered 23 genome-wide significant variants, located at 14 loci. There is little or no overlap between the BPH/LUTS variants and published prostate cancer risk variants. However, 15 of the variants reported here also associate with serum levels of prostate specific antigen (PSA) (at a Bonferroni correctedP < 0.0022). Furthermore, there is a strong genetic correlation, r g = 0.77 (P = 2.6 × 10−11 ), between PSA and BPH/LUTS, and one standard deviation increase in a polygenic risk score (PRS) for BPH/LUTS increases PSA levels by 12.9% (P = 1.6×10−55 ). These results shed a light on the genetic background of BPH/LUTS and its substantial influence on PSA levels. Elderly males are often affected by benign prostatic hyperplasia and associated lower urinary tract symptoms (BPH/LUTS), but their link to prostate cancer risk is not well defined. Here, a genome-wide association study of BPH/LUTS patients from Iceland and the UK found 23 significant variants at 14 loci, and 15 of these variants associate with prostate specific antigen, which is linked to prostate cancer risk.